Long‐term improvements after mindfulness‐based group therapy of depression, anxiety and stress and adjustment disorders: A randomized controlled trial. Issue 4 (3rd July 2018) - Sundquist, Jan; Palmér, Karolina; Memon, Ashfaque A.; Wang, Xiao; Johansson, Leena M.; Sundquist, Kristina
Abstract : Background: Although mindfulness‐based group therapies (MGTs) for depressive, anxiety or stress and adjustment disorders are promising, there is a substantial lack of knowledge regarding the long‐term improvements after such therapies in these common psychiatric disorders. Methods: Two hundred and fifteen patients were randomized in a randomized clinical trial (RCT) (ClinicalTrials.gov ID: NCT01476371) conducted in 2012 at 16 primary healthcare centres in southern Sweden. The patients were randomized to MGT or treatment as usual (TAU) and completed four psychometric self‐rated scales after 8 weeks of treatment. Approximately 12 months after the completion of the 8‐week treatment, the same scales were repeated. Ordinal and generalized linear‐mixed models, adjusted for cluster effects, were used for the analysis. Results: For all four psychometric scales (MADRS‐S [Montgomery‐Åsberg Depression Rating Scale‐S], HADS‐D, HADS‐A [Hospital Anxiety and Depression Scale A and D] and PHQ‐9 [Patient Health Questionnaire‐9]) the scores at the 1‐year follow‐up were significantly improved (all P values <0.001) in both groups. Furthermore, there were no significant differences between the MGT and TAU in the psychometric scores at the 1‐year follow‐up. Conclusions: To the best of our knowledge, this is the first RCT comparing the long‐term improvements after MGT with TAU. Although it cannot be excluded that our findings are a result of the natural course of common psychiatric disorders or other factors, they suggest a long‐term positive improvement after both MGT and TAU.